2010
DOI: 10.1007/s12033-010-9326-x
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Analysis in Multiple Myeloma Research

Abstract: Multiple myeloma (MM) is an incurable plasma cell (PC) malignancy characterized by the accumulation of monoclonal PCs in the bone marrow. For deeper understanding of the molecular mechanisms involved in the development of this disease, the influence of microenvironment, or the prediction of response of tumor PCs to anti-MM treatment, it is possible to use modern technologies for genomic and proteomic analyses. Due to progress in instrumentation, one of the main tools of proteomic analysis is mass spectrometry … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 84 publications
0
12
0
Order By: Relevance
“…Proteomics has been widely employed for MM research. [ 5 6 7 8 9 10 11 12 13 14 ] The potential therapeutic targets in human MM are investigated by differentially profiling of purified MM and normal PCs using two-dimensional (2D) gel electrophoresis. [ 8 ] A total of 43 differentially expressed proteins are identified and six of them are confirmed with Western blotting, including profilin-1, glutathione peroxidase 1, annexin A1, proteasome subunit alpha type-5, proteasome activator subunit-2, and proteasome subunit beta type-10.…”
Section: Introductionmentioning
confidence: 99%
“…Proteomics has been widely employed for MM research. [ 5 6 7 8 9 10 11 12 13 14 ] The potential therapeutic targets in human MM are investigated by differentially profiling of purified MM and normal PCs using two-dimensional (2D) gel electrophoresis. [ 8 ] A total of 43 differentially expressed proteins are identified and six of them are confirmed with Western blotting, including profilin-1, glutathione peroxidase 1, annexin A1, proteasome subunit alpha type-5, proteasome activator subunit-2, and proteasome subunit beta type-10.…”
Section: Introductionmentioning
confidence: 99%
“…Although recent studies have shown that CT antigens are widely expressed at the mRNA and protein levels in MM patients [2], and are correlated with clinical outcomes and shorter survival durations [1,10-12], the patterns of expression and clinical implications of CT antigens have not been fully characterized. Additional data on the expression levels of CT antigens in MM may provide useful information to complement recent developments in diagnostic criteria and prognostic factors, and accelerate the development of effective individualized clinical treatment strategies for MM patients.…”
Section: Introductionmentioning
confidence: 99%
“…MS-based expression screening proteomics contribute to the identification of targeted molecules and their characterization; whereas, quantitative MS approaches will help to measure the protein’s relative or absolute quantity in the identification step, and further quantitative measurement of target protein by MRM, etc. (6). Stable isotope labeling techniques have become very popular in recent years, to perform quantitative mass spectrometry experiments with high precision, and the elucidation of molecular mechanism in multiple biological samples (7).…”
Section: Proteomics Strategiesmentioning
confidence: 99%